2016
DOI: 10.7554/elife.14319
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced metabolic stress in retinal pigment epithelial cells is sufficient to induce photoreceptor degeneration

Abstract: Photoreceptors are the most numerous and metabolically demanding cells in the retina. Their primary nutrient source is the choriocapillaris, and both the choriocapillaris and photoreceptors require trophic and functional support from retinal pigment epithelium (RPE) cells. Defects in RPE, photoreceptors, and the choriocapillaris are characteristic of age-related macular degeneration (AMD), a common vision-threatening disease. RPE dysfunction or death is a primary event in AMD, but the combination(s) of cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
169
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(182 citation statements)
references
References 94 publications
13
169
0
Order By: Relevance
“…A recent report showed that RPE is less stable and less able to support the retina when it is forced to rely on glycolytic rather than mitochondrial metabolism (13). Another recent report supports the importance of mitochondria in RPE by showing that bolstering mitochondrial activity makes these cells more resilient to oxidative damage (14).…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…A recent report showed that RPE is less stable and less able to support the retina when it is forced to rely on glycolytic rather than mitochondrial metabolism (13). Another recent report supports the importance of mitochondria in RPE by showing that bolstering mitochondrial activity makes these cells more resilient to oxidative damage (14).…”
mentioning
confidence: 85%
“…Comparison of M5 citrate and M5 αKG in cells and tissues incubated with 13 C-glutamine shows that reductive carboxylation is more active in RPE than in other cells and tissues (Fig. S2D).…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…In RP, mutations in genes encoding phototransduction enzymes such as rhodopsin and phosphodiesterase 6 (PDE6) impair photoexcitation, creating imbalance between anabolic and catabolic processes that leads to shortening of the outer segments (OS) of photoreceptors and eventually triggering cell death (2,(9)(10)(11)(12). The OS is shed and regenerated daily, but in diseased photoreceptors, there are aberrations in the renewal cycle that lead to significantly shorter OS and subsequent dysgenesis (2,9).…”
Section: Introductionmentioning
confidence: 99%